Eksergoekonomska optimizacija sistema daljinskega hlajenja - Duh Čož, Tjaša (visokošolska dela, 2019)
In this thesis the results of theoretical and experimental analysis of a district cooling system are presented. The general exergoeconomic model of a district cooling system was developed. This model enables the optimal selection of components in the design of a district cooling system as well as the optimization of an existing district cooling system. Different types of the cold production were analysed in this work: cold production by electrically driven compressor chillers and one- or two-stage heat driven absorption chillers, respectively. The target function of the exergoeconomic optimization is the minimum cost of the exergy of cold. The model is based on the exergoeconomic approach where the entire chain of a district cooling system, cold production, distribution and consumption of cold, is included. The energy product, i.e. cold, is validated according to the input exergy, considering the minimum investment, operating and maintenance costs of production, distribution and consumption of cold. The effect of the key design and operation parameters of a district cooling system on the exergoeconomic evaluation criteria of cold supply was evaluated. The model was tested on the existing district cooling system. There, the parameters of the distribution network have been experimentally determined. This was performed by interrupting the operation of a district cooling system and observing the temperature increase in the pipeline due the heat gains. This work reveals, that for district cooling systems with a relatively high cooling demand, an appropriate system design and the optimization, as well as the low prices of electricity and heat, enable good utilization and low price of final product. If these conditions are not fulfilled, the advantages of district cooling systems are reduced.
Keywords: Analiza; Daljinsko hlajenje; Disertacije; dissertations; district cooling; eksergija; eksergijska učinkovitost; eksergoekonomska optimizacija sistema; exergetic efficiency; exergoeconimic optimization; exergy; exergy costs; stroški eksergije